Contractual discourse as the system of speech interaction - Kovalevskaya, Irina I. (Journal of the Belarusian State University. Philology, 2026)
The article deals with the analysis of the contractual discourse in which its parties interact by coordinating their communicative actions. It proves the integration of the systemic and interactive approaches to the study of contractual discourse on the common theoretical and methodological functional basis. The article focuses on the socio-cultural specifics of the communicative actions in the Russian and English contracts based on the denotative structure of their fragments that reflects the links among the content elements.